FRI0352 Small Fibre Neuropathy and Ganglionopathy in Primary Sjogren's Syndrome (PSS). (15th July 2016) - Gupta, V.; Peters, J.; Bombardieri, M.; Radunovic, A.; Sutcliffe, N.
Abstract : Background: Neuropathy occurs in 5–15% of cases with Sjogren's syndrome. Small fibre neuropathy and ganglionopathy are said to be the commonest types of neuropathy in pSS 1 . Small fibre neuropathy is under-recognised since physical examination is often normal and nerve conduction studies show no abnormalities. The increased use of skin biopsy has improved our diagnostic sensitivity. Objectives: To estimate the frequency of small fibre neuropathy and ganglionopathy in pSS patients with neuropathic symptoms using skin biopsy, and to describe the clinical characteristics of these patients. Methods: We identified 25 patients with pSS who were investigated for symptoms of small fibre neuropathy and/or ganglionopathy between January 2010 and December 2015. Patients were assessed by neurological examination, nerve conduction studies, skin biopsy and imaging where appropriate. Results: 13/25 patients had conclusive evidence of small fibre neuropathy (n=12) or ganglionopathy (n=1) on skin biopsy. A further 2/25 patients had borderline skin biopsies suggestive of small fibre neuropathy. 12/13 patients with clear evidence of small fibre neuropathy/ganglionopathy were female. Median age at time of neuropathy diagnosis was 60 years (range 42 – 84, interquartile range 56 – 63). 2 presented initially to a neurologist, and the remainder to a rheumatologist. At least one autoantibody was detected in 11/13. Autoantibody frequencies were ANA 62%, RF 31%, anti-Ro 46%, and anti-La 23%. 7/13 patients met the American-European Consensus Group (AECG) criteria for the diagnosis of definite pSS. 4 of the 6 who did not meet the AECG criteria had a positive ANA or RF. Of these four, 2 had a salivary gland ultrasound (US) characteristic of pSS, and 1 was anti-Ro antibody positive. Both patients with borderline skin biopsies had anti-Ro antibodies and one also had antibodies to La. Median time from diagnosis of pSS to diagnosis of small fibre neuropathy or ganglionopathy was 16 months. In a quarter of patients, the diagnosis of neuropathy was made within 6 months of the diagnosis of pSS. Nerve conduction studies (NCS) did not show a neuropathy in 8/13. In the remaining 5 patients, NCS showed sensory axonal neuropathy in 4 patients, one of whom had diabetes mellitus, and ganglionopathy in 1. In the 2 patients with borderline skin biopsies, NCS suggested a mild sensory axonal neuropathy in one and a mild sensorimotor abnormality in the other. Conclusions: Small fibre neuropathy is an under-recognised complication of pSS in clinical practice. In over half of our pSS patients who presented with neuropathic symptoms, a diagnosis of small fibre neuropathy or ganglionopathy was confirmed. Rheumatologists should consider the possibility of small fibre neuropathy in pSS, and not be falsely reassured by normal clinical examination or nerve conduction studies. 2 patients presented initially to a neurologist. Neurologists should consider Sjogren's syndrome in patients presenting with small fibre neuropathy. References: Birnbaum J. Peripheral nervous system manifestations of Sjögren syndrome, clinical patterns, diagnostic paradigms, etiopathogenesis, and therapeutic strategies. Neurologist 2010;16:287–97. Disclosure of Interest: None declared